Experimental evidence for ultrafast intermolecular relaxation processes in hydrated biomolecules - Ren, Xueguang; Gokhberg, Kirill; Dorn, Alexander (Nature physics, 2018)
The authors study intermolecular Coulomb decay that occurs in a sample of THF and water in a reaction microscope employing triple-coincidence measurements of two ions and one electron. They find that ICD is a previously unconsidered effect between water and other organic molecules that are hydrogen-bonded, with ICD outpacing proton transfer.
Gesehen am 04.02.2020